The socio cultural implications of house-wives rivalry among Yoruba women of South-Western Nigeria (2024)
House wives' rivalry among Yoruba women has over the years become a teething socio-cultural menace that requires a scholarly attention for family stability and a better society where peace and harmony find their footings. It is a known fact that female gender in Yoruba land and Nigeria in general has been marginalized, stereotyped, decimated and humiliated in various ways by their culture that gives the male counterparts such opportunity which has negatively impacted them in various ways like depression, physical disability, psychological trauma and even death. Existing studies on this subject matter, have discussed this menace extensively from the psychological, physiological, sociological, ethics and legal perspectives, with little attention paid to the intra gender violence that are common mostly among house wives in Yoruba land which on many occasions breaks in pieces the social-cultural bond of unity and we- feeling that the people are known for. While many scholars condemn the act in its entirety, as it is believed to be incongruity with rights to dignity of human person, personal liberty, private and family life, others are of the few that Women are to be seen and not to be heard and for this reason, they are to be continually marginalised and treated as second fiddles. This is the gap in study this paper intend to fill Methodologically, the research employs a qualitative method to elicit Information from those involved in family matters, culture, gender issues and human development- Recommendations will be offered where necessary for an improved inter-personal relationship among women for a peaceful society.